Exploring the association between socio-economic and environmental factors and food consumption in Iran: insights from time series data - Pegah Rahbarinejad; Seyyed Reza Sobhani; Negar Sangsefidi; Kiyavash Irankhah; Maryam Mohamadinarab (BMC Public Health)
Abstract Background The nutrition transition—a global shift toward refined, low-fiber diets—is driven by urbanization and economic development, with significant implications for food security. In Iran, where economic volatility (e.g., inflation, sanctions and GDP fluctuations) has altered dietary habits, this study aims to quantify the association of socio-economic and environmental factors with household food consumption patterns. Understanding these dynamics is critical for designing policies that ensure equitable access to healthy diets amid rapid transitions. Method We analyzed secondary data from Iran’s annual Household Income and Expenditure Survey (1991–2019; n = 756,232 households), using a three-stage cluster sampling method to ensure national representativeness. Key variables included urbanization rates, gross domestic product (GDP), food production, inflation, and precipitation, with food consumption measured in daily Adult Male Equivalent (AME) units and categorized into six dietary groups (including; grains, vegetables, fruits, dairy, fats, and meats). Time series regression with ARIMA errors (R 4.1.2) identified drivers of consumption trends. Results In present study, urbanization was positively associated with meat (r = 0.135, P < 0.001) and vegetable (r = 0.086, P = 0.020) consumptions, however negatively associated with grains (r = -0.317, P = 0.025), fruits (r = -0.037, P < 0.001), and dairy (r = -0.0571, P = 0.012) intake. GDP growth raised fruit (r = 0.00007, P = 0.005) and meat (r = 0.00008, P = 0.030) consumptions while lowering grain reliance (r = -0.0007, P = 0.020). Qualitative insights revealed that urban households prioritized convenience and protein-rich foods, whereas rural diets remained grain-heavy due to cost constraints. Inflation increased grain consumption (staple reliance) (r = 0.025, P = 0.003) but decreased fruit intake (r = -0.009, P = 0.007). Additionally, higher precipitation boosted grain consumption (r = 0.004, P = 0.001). Conclusion Iran’s nutrition transition is strongly tied to socio-economic shifts: urbanization and GDP growth favor diversified diets, while inflation exacerbates reliance on cheap staples. Policymakers must prioritize (1) subsidies for nutrient-rich foods, (2) nutrition education, and (3) climate-resilient agriculture to mitigate dietary inequities. These findings offer a template for other economies facing similar transitions.